Sex Pheromone Receptors of Lepidopteran Insects - Yang, Chan; Cheng, Jie; Lin, Jingyu; Zheng, Yuan; Yu, Xiao; Sun, Jinpeng (Frontiers in Ecology and Evolution, 2022)
Lepidopteran insects’ sex pheromone receptors (SPRs) play important roles in chemical communication. In the sex pheromone detection processes, sex pheromone molecule (SPM), SPR, co-receptor (Orco), pheromone binding protein (PBP), sensory neuron membrane protein (SNMP) and pheromone degradation enzyme (PDE) play individual and cooperative roles. Commonly known as butterfly and moth, the Lepidopteran insects are widely distributed throughout the world, most of which are pests. A comprehensive knowledge of Lepidopteran insects SPRs would help the development of sex lure technology and the sex communication pathway research. In this review, we summarized SPRs/Orcos information from 10 families of Lepidopteran insects from corresponding literatures. According to the research progress in the literatures, we speculated evolution of SPRs/Orcos and phylogenetically analyzed the Lepidopteran SPRs and Orcos with neighbor-joining tree, and further concluded the relationship between cluster of SPRs and their ligands; we anayzed the predicted structure features of SPRs and gave our prediction results of SPRs and Orcos with CCTOP and SwissModel; we summarized the functional characterization and of Lepidopteran SPRs and SPR-ligand interaction; and then described progress in the sex pheromone signaling pathways and metabotropic ion channel. Further researches are needed to work out the cyro-EM structure of SPR and the SPR-ligand docking pattern in biophysical perspective, which will directly facilitate understanding of sex pheromone signal transduction pathways and provide guidance in the sex lure technology in field pest control.